Evidence on the political principal-agent problem fromvoting on public finance for concert halls - Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2013)
Principal-agent problems can arise when preferences of voters are not aligned with preferences of political representatives. Often the consequence of the political principalagentproblem is political catering to special interests. In this paper I provide examples of principal-agent problems regarding public spending. The examples concern construction or extension of concert halls in two German cities. Resistance to public funding for the concert halls was particularly strong in electoral districts with large constituencieson the left. The evidence indicates that political representatives were more bourgeois than their constituencies. In the cases studied asymmetric information did not prevailand voters were able to discipline their representatives through referenda that countered the results of voting by political representatives.
Keywords: D72; D78; H72; Z10; 330; Principal-agent problem; referendum; direct democracy; political representation; political ideology; cultural policy